A possible connection between reactive oxygen species and the unfolded protein response in lens development: From insight to foresight - Gao, Lixiong; Jin, Ni; Ye, Zi; Ma, Tianju; Huang, Yang; Li, Hongyu; Du, Jinlin; Li, Zhaohui (Frontiers in Cell and Developmental Biology, 2022)
The lens is a relatively special and simple organ. It has become an ideal model to study the common developmental characteristics among different organic systems. Lens development is a complex process influenced by numerous factors, including signals from the intracellular and extracellular environment. Reactive oxygen species (ROS) are a group of highly reactive and oxygen-containing molecules that can cause endoplasmic reticulum stress in lens cells. As an adaptive response to ER stress, lens cells initiate the unfolded protein response (UPR) to maintain normal protein synthesis by selectively increasing/decreasing protein synthesis and increasing the degradation of misfolded proteins. Generally, the UPR signalling pathways have been well characterized in the context of many pathological conditions. However, recent studies have also confirmed that all three UPR signalling pathways participate in a variety of developmental processes, including those of the lens. In this review, we first briefly summarize the three stages of lens development and present the basic profiles of ROS and the UPR. We then discuss the interconnections between lens development and these two mechanisms. Additionally, the potential adoption of human pluripotent stem cell-based lentoids in lens development research is proposed to provide a novel perspective on future developmental studies.